Electoral Reform and Parliamentary Debates. Issue 4 (28th February 2019) - Høyland, Bjørn; Søyland, Martin G.
Abstract : The early twentieth century saw many democracies adopt proportional representative systems. The textbook explanation, pioneered by Rokkan, emphasize between‐party electoral competition; the rise of the Socialist vote share made Bourgeois parties prefer PR systems to maximize their seat share. While appealing, this account is not entirely compelling. Consequently, scholars are investigating within‐party explanations of support for such reforms. Particularly, Cox, Fiva, and Smith show how list PR enable party leaders to discipline members and build cohesive parties. Relying on roll‐call votes across the Norwegian 1919 electoral reform from two‐round single‐member plurality to closed‐list PR, they show that the internal party cohesion increased following the reform. We investigate how the Norwegian electoral reform changed the content of parliamentary speeches. Comparing speeches from MPs present both before and after the reform, we show how parties become more cohesive in parliamentary debates under list PR than they were under the single‐member‐district system.